Konstruksi Yuridis Tuntutan Ganti Rugi Atas Kekerasan Dalam Rumah Tangga Dalam Perkara Cerai Gugat : (Pendekatan Kewenangan Peradilan Agama) - Natsir Asnawi, M.; Tashin Baaj, Fakhir (Universitas Jambi, Fakultas Hukum, 2025)
The domestic violence-grounded divorce lawsuit in Religious Court has never followed by a claim for compensation despite the wife suffers losses. In fact, the Religious Court has jurisdiction on property disputes or other civil disputes among moslems. The reason of the fact was the intersection authority to proceed claim of compensation due to domestic violence between General Court and Religious Court. Consequently, we have yet to reach an optimum legal protection for the wife due to claim for compensation mechanism still considered under the authority of General Court. The research is a normative research and uses a statutory approach. The problems studied: 1. What is the point of authority intersection to proceed cases of civil tort between Religious Court and General Court?; 2. What is the legal construction of combining divorce cases with claims for compensation for domestic violence? The results of the study indicate that the provisions of Article 50 of Law No. 3 of 2006 provide legal basis for the Religious Court to proceed claim for compensation of its particular case. Claims for compensation in a divorce case are constructed as additional claims for unlawful acts in accordance with the principles of speedy administration justice.